Mapping the Evolution of Quiet Quitting Research: A Five-Year Bibliometric and Topic Modeling Analysis - Rahardian, Dwiky; Yuadi, Imam (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2026)
Quiet quitting has emerged as a significant phenomenon in modern workplace dynamics, reflecting employee disengagement and dissatisfaction with organizational structures. This study provides a comprehensive bibliometric analysis of quiet quitting research over the past five years, utilizing data from the Scopus database and Orange Data Mining for analysis. The findings reveal key themes such as employee engagement, organizational culture, burnout, leadership, and workplace dynamics. The surge in publications related to remote and hybrid work during the period of the pandemic reflects a paradigm shift in academic literature towards the normalization of such work practices. Identifies five key thematic clusters, finding that Quiet Quitting and Organizational Structures and Employee Engagement and Workplace Analysis to be key themes. The insights underscore the need for a multidimensional approach, with implications for how organizations can foster more engaged workplaces by emphasizing supportive policies, kind and engaged leadership, and fairness in task allocation to mitigate the risk of quiet quitting. This study contributes to the literature through a new examination of research patterns to a qualitative research topic that utilized empirical methods drawing on a data-driven investigation highlighting pathways for which both researchers/academics and practitioners might consider exploring going forward.